Analysis of the Purchasing Decision Process Under the Impact of the Pandemic Crisis - Daniela NECHITA (Dunarea de Jos University of Galati, 2021)
The adaptation of the consumer to crisis situations implies, first of all, the mobilization of human, social and material resources in order to overcome the negative effects produced by them, regardless of their duration or scope. These situations generate a series of attitudinal and behavioral changes with implications on the entire economic and social life. Consumer behavior, the component of people's economic behavior is determined by interactions, being a function given by socio-cultural factors and personality traits.